Guanidino-functionalised aromatic electron donors at work: competing hydrogen- and electron-transfer reactions in the course of the synthesis of gold acetylide complexes - Emeljanenko, Dimitri; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2011)
In this work reactions between [AuCl(PPh3)] and HC≡CAr (Ar = phenyl, pyridinyl, biphenyl or p-acetylphenyl) in the presence of the nitrogen base and organic electron donor1,2,4,5-tetrakis(N,N′-dimethyl-N,N′-ethyleneguanidino)benzene (1) were studied. Two different product types were isolated and characterised: the neutral AuI acetylides[Au(C≡CAr)PPh3] and the salts (1)[Au(C≡CAr)2]2. They can be easily separated from each other by crystallisation under different conditions. The yields strongly depend on the applied acetylene. While the first product type underlines the basic properties of 1, the second product type highlights its electron-donor capacity. The experimental results indicate reduction of the C−H protons to H2 and two-electron oxidation of 1. Thermal decomposition of (1)[Au(C≡CAr)2]2 (Ar = Ph) leads back to the neutral guanidine and Au nanoparticles (accompanied by oxidative coupling of the two acetylide ligands).